FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI MASYARAKAT DALAM MEMBUDIDAYAKAN IKAN NILA DI JORONG SIGUHUNG KECAMATAN LUBUK BASUNG KABUPATEN AGAM BARAT - Ramadani, Sherly; Erita, Yeni; Zahara, Leni (STKIP PGRI Sumbar, 2013)
Jorong Siguhung District Of lubuk Basung Regency agam barat representingÂ one of the area which isÂ livelihoodÂ its society conductingÂ fishofÂ Nila and fish seed.Society motivation in fish conducting of nila the unegual, seen from capital and earnings of society.This research aim to to get data, process, analysing and studying about Factors Influencing Motivation Society in Conducting Fish of Nila in Jorong SiguhungÂ District Of lubuk BasungÂ agam barat Regency of seen from1) Capital and 1) Earnings.this Research type is descriptiveÂ korelasional. this Research population is all society which is fish conducting of nila in jorong siguhung distrit of lubuk basung sub âprovince agam barat. Intake of Sampel responder taken pursuant to totalizeing sampling that is withdrawal of sampel done as a whole, sampel in Jorong Siguhung District Of lubuk Basung Regencyagam barat amount to 59 people. Analysis the used is statistical and descriptive of inferensial. Result of this research find 1) There are influence which is signifikan and is positive of capital to Motivation Society in Conducting Fish of Nila in Jorong Siguhung District Of lubuk Basung Regencyagam barat, because t count > t of tables of : ( 14,914 > 1,671) strength of capital relation to society motivation of is including strength ( r = 0, 892) and given contribution equal to 76,6% 2) There are influence which is signifikan and is positive of earnings to Motivation Society In Conducting Fish of Nila in Jorong SiguhungDistrict Of lubuk Basung Regencyagam barat because t count > t of tables of ; ( 2,509 > 1,671), strength of Earnings relation to Motivation society of including is ( = 0,401) and given contribution equal to 0,5%. 3) There are influence of earnings and capital by together to Motivation Society In Conducting Fish of Nila in Jorong Siguhung District Of lubuk Basung Regencyagam barat because F count > F of tables of ; ( 112,436 > 4,01), strength of relation both of the variable to society motivation is including very strong ( r = 0,895) and given contribution 10,9%.